Principles of managerial finance - Gitman, Lawrence J. (New York : Harper & Row, 1985)
The text is designed primarily for the introductory course at the undergraduate level. It may also be used with good results in the core MBA finance course, in management development programs, and in executive study programs.
Includes bibliographical references and index.
hza 27/08/2018
Loans
Keywords: Corporations; Business enterprises